Deformation and Fluid Interactions in the Mineral Fork Diamictites, Antelope Island, Utah - (:unkn) unknown (My University, 2013)
ABSTRACT DEFORMATION AND FLUID INTERACTIONS IN THE MINERAL FORK DIAMICTITES, ANTELOPE ISLAND, UTAH by Kimberly R. Johnson The University of Wisconsin-Milwaukee, 2013 Under the Supervision of Professor Dyanna Czeck Diamictite from the Mineral Fork Formation on Antelope Island, Utah was deformed to various degrees on the footwall of the Willard Thrust Fault during the Sevier Orogeny. The diamictite contains clasts of differing strength resulting in quartzite clasts deformed the least, pink granitic clasts deformed to a greater degree, and softer green gneissic clasts deformed the most. The pink granitic and green gneissic clasts have similar compositions, but deform differently. This preliminary study explores the factors contributing to the different strain responses in the two clast types and the relations between fluids and deformation using three methods: synchrotron Fourier Transform Infrared spectroscopy (FTIR), X-Ray Fluorescence (XRF), and petrographic analyses of microstructures through point counting. An innovative use of a synchrotron infrared beamline is used to measure water content in quartz grains and create grain maps. Analyses of water peak heights and peak areas show that water is present in quartz in quartzite, granitic, and gneissic clasts, with no significant difference in the amount of water between the types. Water is present at all strain magnitudes and often contained in fluid inclusions and microfractures suggesting fluid interaction during deformation. X-Ray Fluorescence (XRF) allows for the chemical analysis (major, minor, and trace elements) of the two clast types. Concentrations of Al2O3 and TiO2, which are relatively immobile, remained approximately the same from low to high strain and are similar to concentrations in the Farmington Canyon Complex, the protolith. This suggests that no volume loss occurred in the clasts with deformation. The concentrations of relatively mobile SiO2 also correlated with the parent rock. A decrease in sodium and increase in magnesium indicate fluid interaction with the clasts resulting in feldspar alteration to phengitic muscovite. Petrographic analyses of these samples reveal microstructures suggesting brittle deformation, dislocation creep (ductile deformation), and recovery processes evidenced by recrystallization and grain boundary migration. Fluid movement was likely aided by both microfractures and movement of dislocations. This exploratory study reveals evidence of fluid-rock interaction in both clast types, through both brittle and ductile deformation mechanisms.
Keywords: Antelope Island; Diamictite; FTIR; Microstructure; Synchrotron; XRF